Aesthetics of deconstruction style. Features of aesthetics of deconstruction style were explored - Kuznetsova, I.; Ponomarenko, V. (Theory and practice of design, 2015)
Comparative analysis of the categories "beautiful" and "ugly" in the style of deconstruction was made, and analyze the nature of their interaction was dne. Based on aesthetic perception and the degree of interaction of aesthetic categories, there was identified three types of formation of forms in deconstruction style. There was defined aesthetic ideals of modernity and the relationship of these ideals with the creative activity of the society.